Psychophysiological characteristics of teenage athletes in cyclic sports - Vedernikova, E. V.; Bugaychuk, T. V.; Galiev, R.R.; Kolodkin, A. S. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to identify the psychophysiological status of teenage athletes involved in cyclic sports.